ROS-Mediated DNA Methylation Pattern Alterations in Carcinogenesis - Wu, Qihan; Ni, Xiaohua (Current Drug Targets, 2015)
Elevated levels of both reactive oxygen species (ROS) and DNA methylation are characteristic of various types of cancer cells. However, the relation between these two is not well understood. Here we will discuss the cause-consequence relationship between ROS and DNA methylation. Cancer research reveals that disregulation of DNA methylation results in regional CpG island hypermethylation and generalized genomic hypomethylation. ROS-induced oxidative stress is associated with both aberrant hypermethylation of tumor suppressor gene (TSG) promoter regions and global hypomethylation. The DNA oxidation structure, 8-hydroxy-2'-deoxyguanosine (8-OHdG), can induce DNA hypomethylation by inhibiting DNA methylation at nearby cytosine bases, while another DNA oxidation structure, 5-hydroxymethylcytosine (5hmC), may achieve active DNA demethylation processes, thus, causing DNA hypomethylation. Recently, it has been found that ROS can function as catalysts of DNA methylation, further accounting for TSG promoter hypermethylation. Moreover, ROS may induce site-specific hypermethylation via either the up-regulation of expression of DNA methyltransferases (DNMTs) or the formation of a new DNMT containing complex. In addition, these ROS-induced DNA methylation pattern alterations have been implicated with not only malignant transformation, but also the progression of numerous tumors. In conclusion, ROS can influence both aspects of DNA methylation changes through different mechanisms, which play an important role of epigenetic regulation in cancer cells. Therefore, the comprehension of mechanisms leading to epigenetic modifications associated with ROS may help better understand the carcinogenesis and progression, as well as aid in the development of potential biomarkers for better cancer diagnostics and novel therapeutic strategies.
Keywords: reactive oxygen species (ROS)